The Token Female - Cindra S. Kamphoff; Suzannah M. Armentrout; Andrew Driska (University of Kansas Libraries, 2010)
Fifteen women who coach NCAA Division I men's teams were interviewed about their experiences coaching men. Six themes emerged after a comprehensive analysis of the interview transcripts: 1) Gender barriers experienced by women coaching men, 2) Obtainment of their position coaching men in unique ways, 3) Women coach only men's minor sports, 4) Characteristics contributing to their success coaching men, 5) Reasons for a lack of women coaching men, and 6) Strategies for change. Findings confirm previous research on women coaching men (i.e., Kane & Stangl, 1991) and point to the tokenism and marginalization that women coaching men experience. Unique findings of this study included that women have to be decorated athletes or coaches to coach men, many of the women in this study were unaware of the opportunity to coach men, and athletic director support is key in the success of women who coach men.